Subsynchronous Oscillation Time-varying Amplitude Frequency On-Line Monitoring Method Based on Sliding Window FFT - Jing YANG; Tong WANG; Junci TANG (Zhongguo dianli)
This paper proposes a time-varying amplitude frequency monitoring method based on sliding window FFT of sub-synchronous oscillation to identify the time-varying modal parameters of the oscillating signals on-line. Firstly, windowed interpolation methods are used to reduce the spectral leakage and fence effect, and decrease the FFT identification errors. Then, through the sliding of the time windows, the signals intercepted by each time window is transformed through FFT to obtain a dynamic sequence of oscillation frequency and oscillation amplitude, that is, varying frequency and amplitude with time. The dynamic sequence of the damping factors is obtained by analyzing and calculating the time-varying oscillation amplitude. Finally, using the ideal non-stationary signals, simulation signals and the measured signals of the power grid as test cases, the comparison results with the Prony and HHT algorithms show that this method not only can eliminate the influence of modal mixing, but also has anti-noise ability. The method can effectively identify the random time-varying oscillation modes and achieve on-line monitoring and analysis of sub-synchronous oscillations.